2015
DOI: 10.1159/000373936
|View full text |Cite
|
Sign up to set email alerts
|

Recharging Red Blood Cell Surface by Hemodialysis

Abstract: Background: Similar as in vascular endothelium the negatively charged glycocalyx of erythrocytes selectively buffers sodium. Loss of glycocalyx (i.e. loss of negative charges) leads to increased erythrocyte sodium sensitivity (ESS) quantified by a recently developed salt-blood-test (SBT). The hypothesis was tested whether a regular 4-hour hemodialysis (4h-HD) alters ESS. Methods:In 38 patients with end stage renal disease (ESRD) ESS was measured before and after 4h-HD, together with standard laboratory and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In vitro , any increase beyond 140 mM Na + stiffens endothelial cells accompanied by a decrease of nitric oxide release (Oberleithner et al, 2007 ). In vivo , plasma Na + in the high physiological range is accompanied by elevated blood pressure (He et al, 2005 ; Suckling et al, 2013 ; Kliche et al, 2015 ), an observation that supports the in vitro results (Oberleithner et al, 2007 ). Since sustained elevated blood pressure affects the morphology of blood vessels, it is assumed to also affect RBC-EC adhesion.…”
Section: Discussionmentioning
confidence: 69%
“…In vitro , any increase beyond 140 mM Na + stiffens endothelial cells accompanied by a decrease of nitric oxide release (Oberleithner et al, 2007 ). In vivo , plasma Na + in the high physiological range is accompanied by elevated blood pressure (He et al, 2005 ; Suckling et al, 2013 ; Kliche et al, 2015 ), an observation that supports the in vitro results (Oberleithner et al, 2007 ). Since sustained elevated blood pressure affects the morphology of blood vessels, it is assumed to also affect RBC-EC adhesion.…”
Section: Discussionmentioning
confidence: 69%
“…Kliche et al . found that the RBC cell surface properties could be partially restored through the dialysis treatment, especially in those individuals with high serum sodium concentrations before the treatment [47]. It has been shown in vitro that sodium concentrations higher than 140 mmol/L impair the glycocalyx and increase adherence of erythrocytes to endothelial cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Another study, carried out with the blood of dialysis patients, showed that the RBC glycocalyx is improved after acute hemodialysis, i.e. salt sensitivity decreases or, in other words, the Na + buffering power of the glycocalyx recovers by a 4-hour hemodialysis of patients suffering from chronic kidney disease [28].…”
Section: Discussionmentioning
confidence: 99%